2016
DOI: 10.1080/15438627.2015.1126280
|View full text |Cite
|
Sign up to set email alerts
|

Effect of 1-year regular Tai Chi on neuromuscular reaction in elderly women: a randomized controlled study

Abstract: This study assessed the effect of 1-year regular Tai Chi (TC) on neuromuscular reaction in elderly women. A total of 41 elderly women (55 years-68 years) completed the study. The TC group (n = 21) performed the 24-form TC, while the control group (C, n = 20) was instructed to read newspapers or watch television when the TC group practised. Electromyogram measurements were conducted before and after intervention. After a year-long intervention, the post-test results of between-group neuromuscular reaction time … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 23 publications
1
17
0
Order By: Relevance
“…Participants who did not have a history of regular exercise in the past three months have taken part in this study. The exclusion criteria, as diagnosed by a physician, were a history of falls, neurological diseases, cardiovascular diseases, Parkinson's symptoms, diabetes, musculoskeletal diseases, and any regular exercise experience since three months ago (7,23,24). After getting the medical certificate, females who diseased (except obesity) and who were taking medications were excluded from the study.…”
Section: Study Populationmentioning
confidence: 99%
See 1 more Smart Citation
“…Participants who did not have a history of regular exercise in the past three months have taken part in this study. The exclusion criteria, as diagnosed by a physician, were a history of falls, neurological diseases, cardiovascular diseases, Parkinson's symptoms, diabetes, musculoskeletal diseases, and any regular exercise experience since three months ago (7,23,24). After getting the medical certificate, females who diseased (except obesity) and who were taking medications were excluded from the study.…”
Section: Study Populationmentioning
confidence: 99%
“…Overweight and obesity are defined as abnormal or excessive fat accumulation and are associated with changes in body geometry and posture disorders (4)(5)(6). Postural stability is essential for the high-quality performance of activities of daily living (ADLs) in older age (7). Impaired postural stability is strongly associated with a risk of falls, and its complications are getting worse with aging (8,9).…”
Section: Introductionmentioning
confidence: 99%
“…In spite of the insignificant effect of Tai Chi on the hip dimension of BMD in our study, some related studies have indicated that it may associated with a significant advantage in pelvic disease, mainly in terms of the reduction of post‐surgical acute and chronic pain and chronic pelvic pain caused by endometriosis (Gizzo et al., ; Lauche et al., ; McGibbon et al., ; Sun et al., ), which we assumed had something to do with the following: Research has shown that nerve injury or entrapment occurring during or following surgical procedures seems to be the main cause for the occurrence of chronic pain after pelvic surgery (Gizzo et al., ). Tai Chi is a complex, multicomponent exercise, and it is possible that it impacts nerve remodeling via multiple processes (Gizzo et al., ).…”
Section: Discussionmentioning
confidence: 59%
“…Tai Chi is a complex, multicomponent exercise, and it is possible that it impacts nerve remodeling via multiple processes (Gizzo et al., ). Randomized studies have reported that Tai Chi exercise can favorably reorganize neuromuscular patterns, resulting in reduced excessive hip compensation, which may alleviative chronic pain after pelvic surgery (Lauche et al., ; McGibbon et al., ; Sun et al., ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation